Anti-CD3 Fab Fragments Enhance Tumor Killing by Human γδ T Cells Independent of Nck Recruitment to the γδ T Cell Antigen Receptor - Juraske, Claudia; Wipa, Piyamaporn; Morath, Anna; Hidalgo, Jose Villacorta; Hartl, Frederike A.; Raute, Katrin; Oberg, Hans-Heinrich; Wesch, Daniela; Fisch, Paul; Minguet, Susana; Pongcharoen, Sutatip; Schamel, Wolfgang W. (Frontiers in Immunology, 2018)
T lymphocytes expressing the γδ T cell receptor (γδ TCR) can recognize antigens expressed by tumor cells and subsequently kill these cells. γδ T cells are indeed used in cancer immunotherapy clinical trials. The anti-CD3ε antibody UCHT1 enhanced the in vitro tumor killing activity of human γδ T cells by an unknown molecular mechanism. Here, we demonstrate that Fab fragments of UCHT1, which only bind monovalently to the γδ TCR, also enhanced tumor killing by expanded human Vγ9Vδ2 γδ T cells or pan-γδ T cells of the peripheral blood. The Fab fragments induced Nck recruitment to the γδ TCR, suggesting that they stabilized the γδ TCR in an active CD3ε conformation. However, blocking the Nck-CD3ε interaction in γδ T cells using the small molecule inhibitor AX-024 neither reduced the γδ T cells’ natural nor the Fab-enhanced tumor killing activity. Likewise, Nck recruitment to CD3ε was not required for intracellular signaling, CD69 and CD25 up-regulation or cytokine secretion by γδ T cells. Thus, the Nck-CD3ε interaction seems to be dispensable in γδ T cells.